A NUMERICAL SOLUTION OF SURFACE WAVE IN POROUS MEDIA - Wiryanto, L.H (MATEMATIKA, 2009)
A model of wave propagation in porous medium is derived, based on the pressure, giving a diffusive-like equation. The model is then solved numerically by a finite difference method. Taylor approximation is applied to the nonlinear term to obtain a diagonal dominant matrix corresponding to the finite difference equations, so that Gauss-Seidel iteration can used to solve the system of equations. As the result, over-damped wave is performed in this paper, related to quality of the medium. Â